Ventral medullary control of rapid eye movement sleep and atonia() - Chen, Michael C. (Exp Neurol, 2017)
Discrete populations of neurons at multiple levels of the brainstem control rapid eye movement (REM) sleep and the accompanying loss of postural muscle tone, or atonia. The specific contributions of these brainstem cell populations to REM sleep control remains incompletely understood. Here we show in rats that viral vector-based lesions of the ventromedial medulla at a level rostral to the inferior olive (pSOM) produced violent myoclonic twitches and abnormal electromyographic spikes, but not complete loss of tonic atonia, during REM sleep. Motor tone during non-REM (NREM) sleep was unaffected in these same animals. Acute chemogenetic activation of pSOM neurons in rats robustly and selectively suppressed REM sleep but not NREM sleep. Similar lesions targeting the more rostral ventromedial medulla (RVM) did not affect sleep or atonia, while chemogenetic stimulation of the RVM produced wakefulness and reduced sleep. Finally, selective activation of vesicular GABA transporter (VGAT) pSOM neurons in mice produced complete suppression of REM sleep whereas their loss increased EMG spikes during REM sleep. These results reveal a key contribution of the pSOM and specifically the VGAT+ neurons in this region in REM sleep and motor control.